CFL Bulbs: Environmentally Friendly and Sustainable? - Zutshi, Ambika (Prabandhan: Indian Journal of Management, 2011)
The purpose of this paper is to document the positive and negative characteristics of using compact fluorescent lamps (CFL) and to raise awareness and debate about the potential negative health effects resulting from prolonged exposure to CFLs. This is a theoretical paper and, primarily, incorporates the literature and the author's experiences of CFLs. Governmental and non-governmental measures in the area of recycling and disposal of CFLs are also presented. This is a relatively new area of research; hence, very limited academic literature is currently available. Discussion of the issue of increased usage of CFLs is timely following heightened debate on greenhouse gas emissions and climate change. Increased debate amongst the policy and decision-makers will assist the public to make an informed decision. It is also anticipated that this debate will put pressure on the manufacturers of all types of bulbs, and government and non-governmental agencies to enhance their own and community initiatives to recycle and/or safely dispose of CFLs. No other similar review of the advantages and weaknesses of using CFLs has been undertaken that encourages the reader and potential users of CFLs to reflect on their choices.